COVID-19 infection among international travellers: a prospective analysis. Issue 6 (24th June 2021) - Lunney, Meaghan; Ronksley, Paul E; Weaver, Robert G; Barnieh, Lianne; Blue, Norman; Avey, Marc T; Rolland-Harris, Elizabeth; Khan, Faisal M; Pang, Jack X Q; Rafferty, Ellen; Scory, Tayler D; Svenson, Lawrence W; et al.
Abstract : Objectives: This report estimates the risk of COVID-19 importation and secondary transmission associated with a modified quarantine programme in Canada. Design and participants: Prospective analysis of international asymptomatic travellers entering Alberta, Canada. Interventions: All participants were required to receive a PCR COVID-19 test on arrival. If negative, participants could leave quarantine but were required to have a second test 6 or 7 days after arrival. If the arrival test was positive, participants were required to remain in quarantine for 14 days. Main outcome measures: Proportion and rate of participants testing positive for COVID-19; number of cases of secondary transmission. Results: The analysis included 9535 international travellers entering Alberta by air (N=8398) or land (N=1137) that voluntarily enrolled in the Alberta Border Testing Pilot Programme (a subset of all travellers); most (83.1%) were Canadian citizens. Among the 9310 participants who received at least one test, 200 (21.5 per 1000, 95% CI 18.6 to 24.6) tested positive. Sixty-nine per cent (138/200) of positive tests were detected on arrival (14.8 per 1000 travellers, 95% CI 12.5 to 17.5). 62 cases (6.7 per 1000 travellers, 95% CI 5.1 to 8.5; 31.0% of positive cases) were identified among participants that had been released from quarantine following a negative test result on arrival. Of 192 participants who developed symptoms, 51 (26.6%) tested positive after arrival. Among participants with positive tests, four (2.0%) were hospitalised for COVID-19; none required critical care or died. Contact tracing among participants who tested positive identified 200 contacts; of 88 contacts tested, 22 were cases of secondary transmission (14 from those testing positive on arrival and 8 from those testing positive thereafter). SARS-CoV-2 B.1.1.7 lineage was not detected in any of the 200 positive cases. Conclusions: 21.5 per 1000 international travellers tested positive for COVID-19. Most (69%) tested positive on arrival and 31% tested positive during follow-up. These findings suggest the need for ongoing vigilance in travellers testing negative on arrival and highlight the value of follow-up testing and contact tracing to monitor and limit secondary transmission where possible.